Methodology for astronaut reconditioning research. (January 2017) - Beard, David J.; Cook, Jonathan A.
Abstract: Space medicine offers some unique challenges, especially in terms of research methodology. A specific challenge for astronaut reconditioning involves identification of what aspects of terrestrial research methodology hold and which require modification. This paper reviews this area and presents appropriate solutions where possible. It is concluded that spaceflight rehabilitation research should remain question/problem driven and is broadly similar to the terrestrial equivalent on small populations, such as rare diseases and various sports. Astronauts and Medical Operations personnel should be involved at all levels to ensure feasibility of research protocols. There is room for creative and hybrid methodology but careful systematic observation is likely to be more achievable and fruitful than complex trial based comparisons. Multi-space agency collaboration will be critical to pool data from small groups of astronauts with the accepted use of standardised outcome measures across all agencies. Systematic reviews will be an essential component. Most limitations relate to the inherent small sample size available for human spaceflight research. Early adoption of a co-operative model for spaceflight rehabilitation research is therefore advised. Highlights: Space research methodology parallels that for small terrestrial populations. Small sample sizes in human spaceflight research pose challenges for study design. Systematic evaluation of individuals may be the most achievable and fruitful approach. Standardised outcome measures are needed across studies. Multi-agency collaboration is vital to enable pooling of data.